Microstructure and mechanical properties of matrix alloy (Ni-Fe-Co-W) derived from tungsten heavy alloys. (2021) - Ravi Kiran, U.; Chinta Babu, U.; Nandi, H.K.; Sarkar, Rajdeep; Nandy, T.K.
Abstract: Present work attempts a correlation between microstructure and mechanical properties of five matrix alloys processed with tungsten content varying from 30 to 50% wt. % and Ni, Fe, Co in the ratio 2:2:1. All the alloys were sintered at 1320 °C for 2 h in hydrogen atmosphere and furnace cooled. The microstructure of the alloy comprised fcc (γ) phase along with tungsten particles. The volume fraction of tungsten increased with increasing tungsten content. Strength ranging from 500 to 600 MPa and ductility from 18 to 20% were obtained in as sintered condition. Forging resulted in increase in strength (1000–1200 MPa) with concomitant loss in ductility (3%). No significant enhancement in tensile properties was observed with heat treatment following forging. Both transgranular and ductile fracture features were observed in the failed tensile specimens. The loss in ductility following swaging/heat treatment was primarily attributed to the presence of increased W particles.